CAPM with various utility functions: Theoretical developments and application to international data - Rihab Bedoui; Houda BenMabrouk (Cogent Economics & Finance, 2017)
This paper presents an extension of the Capital Assets Pricing Model (hereafter CAPM) where various utility functions are applied. Specifically, we propose an overall CAPM beta that accounts for the higher order moments and reflects the investor preferences and attitudes toward risk. We particularly develop CAPM betas for different classes of utility function: the negative exponential utility function, power utility function or 'Constant Relative Risk Aversion (CRRA) Utilities' and hyperbolic utility function or 'HARA Utilities' (hyperbolic absolute risk aversion). In order to validate our theoretical results, we analyze the impact of investors' preferences on the valuation equation. Applying the International CAPM, the results indicate that our utilities-based betas differ largely from the traditional CAPM betas. Moreover, the results confirm the importance of higher order moments on the pricing equation. Finally, the results both empirically and theoretically post to the consistent effect of the risk aversion degree on our utilities-based CAPM.
Keywords: C02; C13; C15; G12; G15; G23; 330; truncated Taylor approximation; negative exponential utility function; power utility function; hyperbolic utility function; risk measure; assets pricing; International CAPM